2013
DOI: 10.3390/polym5041352
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of RC Slabs with Symmetric Openings Using GFRP Composite Beams

Abstract: This paper describes the results of experimental testing of glass fiber reinforced plastic (GFRP) composite beam strengthened reinforced concrete (RC) slabs with two symmetrical openings. Specimens, one-half scale, have been designed and fabricated to reflect the most common RC bathroom slab used in school buildings. The specimen had dimensions of 2000 mm (width) × 150 mm (thickness) × 3000 mm (length) were used with the two openings of 300 mm × 400 mm. The aim of this study is to investigate the most effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Strengthening of RC slabs with symmetrical openings using GFRP composite beams were studied by Yeoi Choi et al [1] with two symmetrical openings and one-half scale with a dimension of slab 3000mm x 2000mm x 150 mm and with two openings of 300 mm x 400 mm. The results shows that there is an increasing the load carrying capacity.…”
Section: Research Significancementioning
confidence: 99%
“…Strengthening of RC slabs with symmetrical openings using GFRP composite beams were studied by Yeoi Choi et al [1] with two symmetrical openings and one-half scale with a dimension of slab 3000mm x 2000mm x 150 mm and with two openings of 300 mm x 400 mm. The results shows that there is an increasing the load carrying capacity.…”
Section: Research Significancementioning
confidence: 99%
“…Fibre Reinforced Polymers (FRP) have been investigated intensively and applied in practice for structural strengthening over the last decade [1,2,3,4,5]. The stiff and brittle adhesives, as epoxy resin [6,7,8] or mineral mortars [9,10,11,12,13,14], are applied in composite strengthening systems composed of various high strength fibers, bonded to concrete and masonry substrates.…”
Section: Introductionmentioning
confidence: 99%
“…These openings will result in diaphragm stiffness reduction and can decrease the load carrying capacity of the member [2,3]. These types of diaphragms are usually designed ignoring opening effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, slabs were only subjected to out-of-plane gravity loads, and the effect of in-plane loads was not considered [8][9][10]22]. Radik et al [24], Choi [3], and Florut et al [4] investigated the effectiveness of different strengthening methods on improving load carrying capacity of slabs with and without openings using GFRP, FRC, and FRP, while slabs were only subjected to out-of-plane loads and again the effect of in-plane loads was not considered. Zhang et al [29] conducted a numerical study on the effect of openings on floor slabs and concluded that presence of openings play an important role in determining the in-plane behavior of the slabs.…”
Section: Introductionmentioning
confidence: 99%